Non–Small-Cell Lung Cancer: Treatment of Late Stage Disease: Chemotherapeutics and New Frontiers - Scheff, Ronald J.; Schneider, Bryan J. (Seminars in Interventional Radiology, 2013)
Systemic therapy should be considered in patients with advanced non–small cell lung cancer (NSCLC) who are no longer amenable to local therapies. Systemic therapy has been shown to improve survival and preserve quality of life in patients with a reasonable performance status. In unselected patients, the standard of care for initial therapy remains platinum-based chemotherapy. At progression, further treatment typically consists of the sequential administration of single-agent therapy, which has also been shown to improve survival and reduce cancer-related symptoms. Molecular biomarkers are essential to guide targeted agents. This analysis requires ample tumor DNA; thus adequate biopsy samples are critical to guide therapeutic options. More biomarkers are currently being validated and may potentially have specific targeted therapy. In the near future, it is likely that rapid multiplexed genotype testing will help reduce the need for large amounts of tumor for analysis and will promote personalized cancer therapy. We review recent changes in the definition of stage IV NSCLC and review current and future systemic therapeutic approaches for patients with advanced disease.
Keywords: non–small cell lung cancer; chemotherapy; systemic therapy; targeted therapy